2021
DOI: 10.1016/j.jbc.2021.100402
|View full text |Cite
|
Sign up to set email alerts
|

Selective coactivation of α7- and α4β2-nicotinic acetylcholine receptors reverses beta-amyloid–induced synaptic dysfunction

Abstract: Beta-amyloid (Aβ) has been recognized as an early trigger in the pathogenesis of Alzheimer's disease (AD) leading to synaptic and cognitive impairments. Aβ can alter neuronal signaling through interactions with nicotinic acetylcholine receptors (nAChRs), contributing to synaptic dysfunction in AD. The three major nAChR subtypes in the hippocampus are composed of α7-, α4β2-, and α3β4-nAChRs. Aβ selectively affects α7- and α4β2-nAChRs, but not α3β4-nAChRs in hippocampal neurons, resulting in neuronal hyperexcita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 111 publications
4
59
0
Order By: Relevance
“…To identify the binding site for Aβ 42, we performed the exhaustive scan of the whole extracellular receptor domain using ClusPro. The best-scoring poses (8/10) converged to the site, which partially overlaps with the reported α-BTX binding sites, consistent with the reports on α7 receptor activation via orthosteric modality reversing the Aβ 42 binding [20]. Therefore, we concluded that the amyloid β (Aβ42) binding site overlaps with that for α-BTX.…”
Section: The Effect Of Dupα7 Subunits On Macromolecular Ligand Bindingsupporting
confidence: 87%
See 2 more Smart Citations
“…To identify the binding site for Aβ 42, we performed the exhaustive scan of the whole extracellular receptor domain using ClusPro. The best-scoring poses (8/10) converged to the site, which partially overlaps with the reported α-BTX binding sites, consistent with the reports on α7 receptor activation via orthosteric modality reversing the Aβ 42 binding [20]. Therefore, we concluded that the amyloid β (Aβ42) binding site overlaps with that for α-BTX.…”
Section: The Effect Of Dupα7 Subunits On Macromolecular Ligand Bindingsupporting
confidence: 87%
“…For Aβ 42 interactions, the ligand residues that interacted with the receptor binding sites were located in the C-terminal regions of the Aβ 42 monomer (Table 2). The predicted binding affinity of the Aβ 42 to the binding site comprising two α7 subunits (the canonical receptor) was in the low nM range, consistent with available experimental data [20]. As a comparison, α-BTX was predicted to bind to the canonical a7 binding sites with one order of magnitude lower (high pM range) than Aβ.…”
Section: The Effect Of Dupα7 Subunits On Macromolecular Ligand Bindingsupporting
confidence: 78%
See 1 more Smart Citation
“…The Aβ–α4β2 nAChR interaction interface is formed by the 11-EVHH-14 and 35-HAEE-38 sites of Aβ and the α4 subunit of α4β2 nAChR, respectively [ 5 ]. The 11-EVHH-14 region of Aβ also plays a critical role in Aβ binding to α7 nAChRs; however, the exact interface of the Aβ-α7 nAChR complex is unknown [ 4 , 6 , 29 , 37 , 38 ]. The 11-EVHH-14 region has a relatively rigid backbone conformation in soluble Aβ monomers [ 39 , 40 ] and zinc-bound dimers [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…ACh acts via two classes of receptors: ionotropic nicotinic receptors (nAChRs) and metabotropic muscarinic receptors (mAChRs). The major subtypes of nAChRs, nAChRα7 and nAChRα4β2 regulate synaptic plasticity [ 12 ]. The activity of cholinergic neurons and ACh production by cholinergic neurons decrease in AD patients, and administration of anticholinergic drugs is associated with the development of AD [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%